STRATEGI PENGUATAN NILAI MULTIKULTURAL DI IAIN MANADO DALAM MANAJEMEN PENDIDIKAN TINGGI ISLAM - Dwi Ajeng Maulidya Makalao; Asy'ari Asy'ari; Acep Ruskandar; Uus Ruswandi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This study explores the strategy of strengthening multicultural values at IAIN Manado within the framework of Islamic higher education management. The research is based on the urgency of multicultural education as a response to Indonesia’s diverse sociocultural landscape. It addresses three main questions: how multicultural education is conceptualized at IAIN Manado, what strategies and practices are implemented, and what challenges and opportunities are encountered. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. Findings reveal that multicultural education is embedded in institutional policies, academic practices, and campus social activities, such as culturally responsive curriculum integration, interfaith forums, and gender equality training. Lecturers' strategies reflect equitable and diversity-responsive pedagogy. Despite challenges such as limited gender-inclusive facilities and lack of intercultural communication training, institutional commitment and local community involvement provide strategic opportunities. These findings showcase a model of inclusive Islamic higher education that is contextually relevant to fostering a multicultural society.